Relationship between internet addiction and social skill level in children at secondary school level - Kuzlu Ayyıldız, Tülay; Harkın Gemicioğlu, Şirin; Topçu, Fatma; Demir, Aleyna; Kaya, Kübra Nur (Journal of Dependence, 2023)
Objective: The aim of this study is to reveal the relationship between internet addiction and social skill levels in secondary school students and to examine how these variables differ according to demographic and internet usage characteristics. Method: This descriptive and cross-sectional study was conducted with 500 students who voluntarily agreed to participate in the study at a secondary school in a province. Data; It was collected with “Student Information Form”, “Internet Addiction Scale” and “Matson Social Skills Scale”. Results: There was a significant difference between students’ Internet addiction scale scores and gender, grade level, father’s education level, school success and duration of internet use. A significant difference was found between Matson social skill scale scores and gender, success at school, membership in social networking sites and duration of internet use. There was a negative relationship between students’ internet addiction scale scores and Matson social skills scale positive sub-dimension scores, and a positive significant relationship between negative sub-dimension scores. Conclusion: Internet addiction levels of students are affected by socio-demographic and internet usage characteristics. As the level of internet addiction increases, the level of social skills decreases. According to these results, it has been suggested that students, families, teachers and nurses as health professionals have various duties in terms of risks in internet use and that stakeholders should cooperate in common areas.